The Characteristics and Mortality of Osteoporosis, Osteomyelitis, or Rheumatoid Arthritis in the Diabetes Population: A Retrospective Study - Jin-Feng Huang; Qi-Nan Wu; Xuan-Qi Zheng; Xiao-Lei Sun; Chen-Yu Wu; Xiao-Bing Wang; Chen-Wei Wu; Bin Wang; Xiang-Yang Wang; Michael Bergman; Ai-Min Wu (International Journal of Endocrinology)
Background. Patients with diabetes mellitus are prone to develop osteoporosis, osteomyelitis, or rheumatoid arthritis (RA). Furthermore, the presence of these complications in those with diabetes may lead to higher mortality. The aim of our study was to assess characteristics and mortality of osteoporosis, osteomyelitis, or rheumatoid arthritis in individuals with diabetes. Methods. We analyzed osteoporosis, osteomyelitis, and RA deaths associated with diabetes from 1999–2017 using the CDC WONDER system (CDC WONDER; https://wonder.cdc.gov). We used ICD-10 codes to categorize the underlying and contributing causes of death. Crude mortality rates (CMR) and age-adjusted mortality rates (AAMR) per 1,000,000 person-years were calculated. Results. The AAMR for osteoporosis in the population with diabetes was significantly higher in females (AAMR: 4.17, 95% CI: 4.10–4.24) than in males (AAMR: 1.12, 95% CI: 1.07–1.16). Deaths due to osteoporosis increased gradually from 1999, peaked in 2003 (AAMR: 3.78, 95% CI: 3.55–4.00), and reached a nadir in 2016 (AAMR: 2.32, 95% CI: 2.15–2.48). The AAMR for RA associated with diabetes was slightly higher in females (AAMR: 4.04, 95% CI: 3.98–4.11) than in males (AAMR: 2.45, 95% CI: 2.39–2.51). The mortality rate due to RA increased slightly from 1999 (AAMR: 3.18, 95% CI: 2.97–3.39) to 2017 (AAMR: 3.20, 95% CI: 3.02–3.38). The AAMR for osteomyelitis associated with diabetes was higher in males (AAMR: 4.36, 95% CI: 4.28–4.44) than in females (AAMR: 2.31, 95% CI: 2.26–2.36). From 1999 to 2017, the AAMR from osteomyelitis in this population was 2.63 (95% CI: 2.44–2.82) per 1,000,000 person-years in 1999 and 4.25 (95% CI: 4.05–4.46) per 1,000,000 person-years in 2017. Conclusions. We found an increase in the age-adjusted mortality rates of RA and osteomyelitis and a decrease of osteoporosis associated with diabetes from 1999 to 2017. We suggest that increased attention should therefore be given to these diseases in the population with diabetes, especially in efforts to develop preventative and treatment strategies.